Differentially regulated pools of aquaporin-4 (AQP4) proteins in the cerebral cortex revealed by biochemical fractionation analyses - Julia Ramadhanti; Tomoko Yamada; Masato Yasui; Mutsuo Nuriya (Elsevier, 2021)
Aquaporin-4 (AQP4) is a predominant water channel in the central nervous system. It regulates water movement in the brain and has been suggested to play critical roles in various pathological conditions. However, the molecular mechanisms underlying its regulation are not yet well understood. In this study, we biochemically characterized AQP4 in the brain using acute cortical brain slices prepared from mice. Using biochemical fractionation, we found that AQP4 is enriched in the detergent-resistant membrane (DRM) fraction that is not soluble in 1% Triton X-100. In contrast, β-dystroglycan and syntrophin, which are part of the dystrophin complex in the brain, primarily reside in the non-DRM fraction. DRM enrichment of AQP4 is insensitive to cholesterol depletion, suggesting that it is not tightly associated with lipid rafts. Furthermore, AQP4 in the DRM fraction is more enriched in the M23 isoform than in the non-DRM fraction. Finally, by employing oxygen-glucose deprivation (OGD), an in vitro model of ischemia, we examined the molecular changes of AQP4. Under OGD conditions, a reduction in AQP4 in the DRM fraction was observed before the total AQP4 protein level dropped. Our data therefore highlight the characteristics of two pools of AQP4 that are distinctly regulated under ischemic conditions.